Revisiting the income-health nexus: the importance of choosing the 'right' indicator - Nicolas R. Ziebarth; Joachim R. Frick (Institute for the Study of Labor (IZA), 2010)
We show that the choice of the welfare measure has a substantial impact on the degree of welfare-related health inequality. Combining various income and wealth measures with different health measures, we calculate 80 health concentration indices. The influence of the welfare measure is more pronounced when using subjective health measures than when using objective health measures.
Keywords: D31; I10; I12; 330; Health inequality; concentration index; income measurement; SOEP; Gesundheit; Sozialer Indikator; Disparitätsmaß; Einkommensverteilung; Einkommen; Messung; Wohlfahrtseffekt; Theorie; Schätzung; Deutschland